The Perception of Using TED Talks in Enhancing College Students’ Listening Skill for The Fourth Semester of Health Administration Students at STIKes RS Husada Academic Year 2023 –2024 - Ludovikus Ludovikus; Yurita Mailintina; Ellynia Ellynia (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
This article presents survey data from 21 students from Bachelor’s Degree of Health Administration about the perception of using TED talks. The objective of the study was to know the students’ perceptions of using TED Talks in improving listening skill for the fourth semester of Health Administration students at STIKes RS Husada Academic Year 2022 – 2023. In the perception of convenience, the mean scores for all statements ranged from 2.05 to 2.33, which suggests a positive perception of convenience. The standard deviations were relatively low, indicating a certain level of agreement among the students. In the perception of benefits, the mean scores for all statements ranged from 1.86 to 2.10, indicating positive perceptions of benefits. The standard deviations were relatively low, suggesting a certain level of agreement among the students. In the perception of interests, the mean scores for all statements were around 2.00, indicating positive perceptions of interests. The standard deviations were relatively low, suggesting a certain level of agreement among the students. In conclusion, the findings from the study indicate that the students have positive perceptions regarding the convenience, benefits, and interests associated with using TED Talks for learning and practicing listening skills.